In vitro shear bond strength over zirconia and titanium alloy and degree of conversion of extraoral compared to intraoral self-adhesive resin cements - Vincent Fouquet; Claire-Adeline Dantagnan; Sarah Abdel-Gawad; Elisabeth Dursun; Jean-Pierre Attal; Philippe François (BDJ Open, 2023)
Abstract Objective Evaluation of the Shear bond strength over zirconia and titanium alloy and degree of conversion of extraoral compared to intraoral self-adhesive resin cements. Materials and methods Nine bonding protocols were carried out on zirconia 4Y-TZP and titanium alloy (Ti-6Al-4V). Seven resin cement (one extraoral and six intraoral) were tested in the shear bond strength test and the degree of conversion measurements. Results The significantly highest value was obtained for Monobond Plus + Multilink Hybrid Abutment, the extraoral resin cement for both titanium alloy (35.1 MPa) and zirconia (32.9 MPa). For each resin, significantly higher DC values were obtained for the dual-cure mode compared with the self-cure mode. Regardless of the cure mode, Nexus Universal reached the highest DC (78.4%). Discussion/Conclusions In this study, the extraoral self-curing resin cement showed the higher bond strength values on zirconia and titanium alloy when associated with a universal primer. Some intraoral dual-cure resin cements showed closed performances when used with universal primers. There is no direct correlation between the degree of conversion of the resin cement and the shear bond strength obtained on the prosthetic materials tested.